2013
DOI: 10.1097/anc.0b013e318278b907
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of Neonatal Peripherally Inserted Central Catheter (PICC) Practices

Abstract: This extensive national survey of NICU PICC practices showed wide variation in multiple aspects of PICC insertion and maintenance. A gap between the evidence and current practice was evident in many facets of training, insertion techniques, and maintenance processes. The data suggest a need for an increase in awareness of clinicians of current practice guidelines and standards and the need for further research to develop an evidence basis for many aspects of PICC care where lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
64
0
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 55 publications
1
64
0
14
Order By: Relevance
“…5 Further research is required to determine whether the algorithm can be refined to identify earlier stages of IV infiltration. Grade 4 infiltrations were reduced and statistical significance ( P = .00021) was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…5 Further research is required to determine whether the algorithm can be refined to identify earlier stages of IV infiltration. Grade 4 infiltrations were reduced and statistical significance ( P = .00021) was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…It was identified a lack of studies about this theme related to this specific population, being this, one of the limiting factors of the study. (9,(24)(25)(26)(27) Adherence to the use of bundle has shown significant results in reducing CLABSI in NICU, linked to permanent education practices. (9,26) A meta-analysis aimed at evaluating the efficacy of bundles of CLABSI prevention in neonatal, pediatric and adult Intensive Care Unit, identified that this strategy implementation in different countries presents positive results in costs reduction.…”
Section: Discussionmentioning
confidence: 99%
“…These gauges are recommended for higher safety. (24) The third item included the disinfection of the stopcocks and connections at each handling, with 70% alcohol by means of the strict friction with at least five circular movements. Such care provides significant reductions in the CLABSI, however, there is no consensus on the use of 70% alcohol and the alcoholic antiseptic solution of chlorhexidine gluconate in neonatology.…”
Section: Discussionmentioning
confidence: 99%
“…12 , 13 Other surveys were actual reports of their own centers' practices and did not reflect multiple centers. 4 This national survey represented 25% of the level III NICUs from 43 states. 16 In 2010, this author conducted a national survey of neonatal PICC practices in the United States, which was published in 2013.…”
mentioning
confidence: 99%